Dynamics of Soluble Factors and Double-Negative T Cells Associated with Response to Renal Denervation in Resistant Hypertension Patients - Silva, Joana Delgado (2022)
The role of the immune system, and hence inflammation, in the pathophysiology of hypertensive patients is not clear. Until now, most clinical and biochemical parameters have failed to predict a positive response to renal denervation (RDN). Our aim was to evaluate the immune response in a cohort of patients treated by RDN, through the analysis of cytokine, chemokine, and growth factor behavior. A population of 21 resistant hypertension patients, treated by RDN, was evaluated at six months and one year. Response was defined as a drop of ≥5 mmHg in ambulatory blood pressure monitoring. Sixty-seven percent and 81% of patients clinically responded after six months and one year, respectively. There were no complications or safety issues. Plasmatic levels of 45 cytokine, chemokine, and growth factors were quantified at four different times, pre- and post-procedure. Baseline characteristics were similar between groups, except that active smoking was more frequent in non-responders at one year. Regulated on activation, normal T cell expressed, and secreted (RANTES/CCL5) levels were significantly lower in responders, both at baseline and at 30 days (p = 0.037), and a level ≤15,496 pg/mL was the optimal cutoff, for prediction of a response. IL-15, IL-17A, IL-27, and leukemia inhibitory factor varied significantly in time, with an acute rise being observed 24 h after RDN. Our group has previously showed that HLA-DR+ double-negative (DN) T cells were significantly lower in responders. There was a positive correlation between IL-13, -27, and -4, and DN T cells, and a negative correlation between the latter and SDF-1α and TNF-α, at baseline. Low plasmatic levels of the chemokine RANTES/CCL5 was the most significant result associated with RDN response and may help to identify the best candidates among patients with true resistant hypertension. Pro-inflammatory cytokines correlated negatively with DN T cells in responders, a finding compatible with an enhanced inflammatory milieu present in this extremely high cardiovascular risk cohort.